Healing experiences of women survivors of childhood sexual abuse / Chen Lee Ping - Chen, Lee Ping (2012)
This study aimed to explore and gain an in-depth understanding of the healing experiences encountered by Malaysian women survivors who had gone through childhood sexual abuse. A qualitative research using transcendental-phenomenological research design was used to explore the healing experiences encountered by 7 women survivors with a history of childhood sexual abuse. The process of collecting data involved 3 stages of in-depth interview sessions with each of the survivors. A total of 21 in-depth interview sessions were carried out with each session ranging from 40 to 100 minutes. The method of data analysis was based on Moustakas’s (1994) phenomenology data analysis. Outcome of this study unveiled 9 themes of healing experiences encountered by the 7 women survivors. Among the 9 themes of healing, 5 themes were the healing processes the women survivors had gone through in their healing journey. They were: “confronted with struggles,” “channels to express and reflect,” “forgiveness,” “acceptance,” and “let go and move on.” The other 4 themes were the healing contributors: “receive social support,” “helping self (resiliencies),” “helping other,” and “spirituality.” The study revealed women survivors had gone through several healing processes in the journey of recovering from childhood sexual abuse. A smooth healing process required the presence of the healing contributors, which played a significant role in facilitating the healing processes. Healing processes and healing contributors are interconnected and both worked hand in hand to assist women survivors to obtain healing from childhood sexual abuse. Research outcomes provide additional insights into understanding healing from childhood sexual abuse, in particular from the women survivors’ perspective. Implications of the study to helping professionals and future researchers are discussed.